Rethinking the Concept of Disability from the Perspective of Javanese Local Culture - Imanuel Teguh Harisantoso (INKLUSI, 2026)
Javanese culture provides a unique epistemological framework for understanding disability. Within Javanese cosmology, disability is not limited to bodily impairment but is embedded in symbolic, ritual, and religious structures, as reflected in figures such as Palawijan and the Punakawan. This study aims to clarify, reinterpret, and reclaim the place of disability within Javanese thought. Colonial modernity introduced epistemic ruptures, establishing hierarchical knowledge systems and medical frameworks that defined disability as illness or abnormality. Such models severed disability from its spiritual and cosmological dimensions and privileged utilitarian, medical interpretations. Employing cultural hermeneutics, supported by theories of *othering* and orientalism, this research examines how colonial knowledge marginalized indigenous meanings. The findings show that disability in Javanese culture is closely associated with spiritual potency and moral agency. Persons with disability are often regarded as *orang sakti*, individuals with supernatural power who mediate justice, balance, and welfare. Disability is a source of sacred power essential for maintaining cosmological harmony and communal well-being. Budaya Jawa menyediakan kerangka epistemologis yang unik untuk memahami disabilitas. Dalam kosmologi Jawa, disabilitas tidak terbatas pada gangguan tubuh semata, tetapi tertanam dalam struktur simbolik, ritual, dan religius, sebagaimana tercermin dalam figur seperti Palawijan dan Punakawan. Penelitian ini bertujuan untuk memperjelas, menafsirkan kembali, dan merebut kembali posisi disabilitas dalam pemikiran Jawa. Modernitas kolonial memperkenalkan keterputusan epistemik dengan membangun sistem pengetahuan yang hierarkis serta kerangka medis yang mendefinisikan disabilitas sebagai penyakit atau abnormalitas yang memerlukan rehabilitasi. Model-model tersebut memutus disabilitas dari dimensi spiritual dan kosmologisnya, serta mengutamakan tafsir yang utilitarian dan medis. Dengan menggunakan hermeneutika budaya, yang didukung teori *othering* dan orientalisme, penelitian ini menelaah bagaimana pengetahuan kolonial memarginalkan makna-makna lokal. Temuan penelitian menunjukkan bahwa disabilitas dalam budaya Jawa sangat berkaitan dengan potensi spiritual dan agensi moral. Penyandang disabilitas kerap dipandang sebagai *orang sakti*, yakni individu yang memiliki kekuatan supranatural dan berperan sebagai penengah keadilan, keseimbangan, serta kesejahteraan. Disabilitas adalah sumber kekuatan sakral yang penting untuk menjaga harmoni kosmologis dan kesejahteraan komunitas.